Health Uninsurance in rural America: A partial equilibrium analysis - William Nganje; Kwame Asiam Addey (Health Economics Review, 2019)
Background: The cost of rural health continues to be high in the United States despite an overall improvement in national health insurance enrolment. Stakeholder's perception of adverse selection remains a paramount culprit in the challenges of rural insurance markets. Risk attitude has been revealed as an alternative for measuring this phenomenon, given the 2014 prohibition law on pre-existing conditions and a subsequent repeal in 2018 accompanied by extensive debate among congress. We examine the existence of adverse selection in rural insurance markets by comparing the effects of pre-existing or chronic health conditions and risk attitudes in a Principal-Agent model. Results: Using multinomial logit and complementary log-log binomial link models in a Principal-Agent framework, our results indicate that there is adverse selection in rural health insurance markets if pre-existing conditions are considered, but risk attitudes yield contrary effects. Conclusions: The major policy implication from this study is that respondents who have pre-existing/chronic conditions tend to patronise health insurance with a higher probability than other counterparts and therefore insurers are likely to incur losses given the law on pre-existing conditions as private information. The 2018 law on the exclusion of individuals with pre-existing conditions may be beneficial to the insurance companies at the expense of the populace. Hence, we suggest that market incentive-based programs should be encouraged to minimize rural health uninsurance.
Keywords: D82; I11; I13; 330; Pre-existing conditions; Principal-agent model; Rural health uninsurance; Complementary log-log binomial; Spence-Mirrlees condition